Research on The Pore-Forming Mechanism of Porous Tial Intermetallics with (NH4)2CO3. (October 2019) - Li, Xide; Sun, Liangbo; Liu, Yuzuo; Yang, Junsheng
Abstract: Porous TiAl intermetallic compound is a material with excellent properties, which could be applied to various fields. However, the disadvantage of current porous TiAl intermetallics is that the permeate flux is low. In this paper, (NH4 )2 CO3 was selected as pore-forming agent to fabricate porous TiAl intermetallics by activation reactive sintering. After that, the effect of pore former (NH4 )2 CO3 content and pore-forming mechanism were investigated. The results indicated that the pore former (NH4 )2 CO3 is benefit for the formation of through-holes in porous TiAl intermetallics, and the Kirkendall partial diffusion effect has great influence on the pore formation.